(untitled) (Research, Society and Development, 2022)
The aim of the study was to characterize the profile of recipients of massive blood transfusion and verify adherence to the massive transfusion protocol by the healthcare team based on the regulations established by Resolution n 34 of 2014. This is a documental, retrospective and comparative study, of quantitative approach, in which transfusion requisitions filed by the hospital were analyzed. The data collected correspond to the period from December 2018 to August 2019, and these were analyzed using descriptive statistics. It was identified that most occurrences of massive transfusion were indicated for male patients, as a result of external causes. Moreover, we observed flaws in the filling of transfusion requisitions. The study showed the need for improvements in the hemotherapy area, in order to promote safe and quality care to patients, as well as the need for training professionals working in this area.